Privatisation of german rail: Requirements for the organisational structure of the railway from a spatial planning perspective - M. Stielike, Jan (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
The railway is a key part of the services of general interest and fulfils important functions for the common welfare. But against the background of the states’ limited financial resources the rail also has to work cost-effectively. This polarity can be solved in the best way by a transition from the “accountability for services” to the “accountability for regulation” of the state. This means that the provision of transport services is put out to tender under predefined conditions and for a limited period of time. From a spatial planning perspective the rail network has to set up high-capacity links between economic centres as well as connections to peripheral spaces.
Keywords: Infrastructure; Transport; Railway; Services of general interest; Privatisation; Regulation